Motoric cognitive risk syndrome as a predictor of incident disability: A 7 year follow-up study - Bai, Anying; Bai, Weimin; Ju, Hepeng; Xu, Weihao; Lin, Zhanyi (Frontiers in Aging Neuroscience, 2022)
Background Though motoric cognitive risk syndrome (MCR) share risk factors with disability, whether it predict disability remains understudied. Objectives This study aims to examine the association between MCR and incident disability. Design Longitudinal study. Methods MCR was defined as subjective cognitive complaints and objective slow gait speed. Two subtypes of MCR were defined by whether memory impairment (MI) was also present, MCR-MI and MCR-non-MI. Incident activities of daily living (ADL) disability and instrumental activities of daily living (IADL) disability were outcome measures. Multiple logistic regression analysis was used to assess the independent effect of MCR at baseline on the odds of ADL/IADL disability at a 7 year follow-up. Results Among the subjects who were not disabled at baseline and followed for 7 years, 34.66% reported incident ADL disability, and 31.64% reported incident IADL disability. Compared with participants without MCR at baseline, those with MCR had 58% increased odds of incident ADL disability (OR=1.58, 95% CI: 1.19–2.09) and 46% increased odds of incident IADL disability (OR=1.46, 95% CI: 1.13–1.88) after 7 years. MCR-non-MI was associated with a 56.63% increased risk of ADL disability and a 34.73% increased risk of IADL disability. MCR-MI was associated with an even higher risk of IADL disability (OR = 2.14, 95% CI: 1.18–3.88). Conclusions MCR is an independent risk factor for both incident ADL and IADL disability. MCR-MI predicts a higher risk for disability than MCR-non-MI. Early identification of MCR among older adult is recommended and may decrease future risk of disability.